2010
DOI: 10.1590/s1517-83822010000200017
|View full text |Cite
|
Sign up to set email alerts
|

A survey for maintenance of virulent newcastle disease virus-free area in poultry production in Brazil

Abstract: These results showed that Brazil preserves the virulent NDV-free status for commercial flocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
3
3
0
3
Order By: Relevance
“…The diseases prevalent in the Dormaa District do not deviate from the common diseases found within the poultry industry in other parts of the world (McPherson, 1956;Adene, 1990;Wilson, 2007;and Orsi et al, 2010).…”
Section: Diseases and Control Measuresmentioning
confidence: 87%
“…The diseases prevalent in the Dormaa District do not deviate from the common diseases found within the poultry industry in other parts of the world (McPherson, 1956;Adene, 1990;Wilson, 2007;and Orsi et al, 2010).…”
Section: Diseases and Control Measuresmentioning
confidence: 87%
“…The data presented in this study show that none of the 12 isolated samples were pathogenic, with ICPI < 0.70; similar results were obtained by Orsi et al (18,20). The results obtained in the present study showed that non-export industrial poultry from the four studied Brazilian federative units nonpathogenic Newcastle disease virus was found, as established in the standard postulated by  the International Animal Health Code.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we isolated NDV in healthy birds with a frequency from 0 to 1.7% for flocks and from 0% to 100% by geographic region; similar results were obtained by Orsi et al (20) with the percentage of isolation per flocks of 0.44% and 53.3% in the Southeastern region. However, another research by Orsi et al (18) resulted in 7.6% per flock and 58.4% in the Southeastern region.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some other symptomatic and asymptomatic birds had sudden death (Clavijo et al 2000, Catroxo et al 2012. Brazil has the status of free of pathogenic NDV in commercial poultry, and in the suspect of the disease the notification to the official veterinary service in the country is mandatory (Brasil 2007, Orsi et al 2010.…”
Section: Introductionmentioning
confidence: 99%